Integration of longitudinal and circumferential strain predicts volumetric change across the cardiac cycle and differentiates patients along the heart failure continuum - Samuel, T. J.; Oneglia, Andrew P.; Cipher, Daisha J.; Ezekowitz, Justin A.; Dyck, Jason R. B.; Anderson, Todd; Howlett, Jonathan G.; Paterson, D. I.; Thompson, Richard B.; Nelson, Michael D. (Université d'Ottawa | University of Ottawa, 2023)
Abstract Background Left ventricular (LV) circumferential and longitudinal strain provide important insight into LV mechanics and function, each contributing to volumetric changes throughout the cardiac cycle. We sought to explore this strain-volume relationship in more detail, by mathematically integrating circumferential and longitudinal strain and strain rate to predict LV volume and volumetric rates of change. Methods Cardiac magnetic resonance (CMR) imaging from 229 participants from the Alberta HEART Study (46 healthy controls, 77 individuals at risk for developing heart failure [HF], 70 patients with diagnosed HF with preserved ejection fraction [HFpEF], and 36 patients with diagnosed HF with reduced ejection fraction [HFrEF]) were evaluated. LV volume was assessed by the method of disks and strain/strain rate were assessed by CMR feature tracking. Results Integrating endocardial circumferential and longitudinal strain provided a close approximation of LV ejection fraction (EFStrain), when compared to gold-standard volumetric assessment (EFVolume: r = 0.94, P < 0.0001). Likewise, integrating circumferential and longitudinal strain rate provided a close approximation of peak ejection and peak filling rates (PERStrain and PFRStrain, respectively) compared to their gold-standard volume-time equivalents (PERVolume, r = 0.73, P < 0.0001 and PFRVolume, r = 0.78, P < 0.0001, respectively). Moreover, each integrated strain measure differentiated patients across the HF continuum (all P < 0.01), with the HFrEF group having worse EFStrain, PERStrain, and PFRStrain compared to all other groups, and HFpEF having less favorable EFStrain and PFRStrain compared to both at-risk and control groups. Conclusions The data herein establish the theoretical framework for integrating discrete strain components into volumetric measurements across the cardiac cycle, and highlight the potential benefit of this approach for differentiating patients along the heart failure continuum.